Production risks, risk preference and contract farming: Impact on food security in India - Mishra, Ashok K.; Kumar, Anjani; Joshi, Pramod Kumar; D'Souza, Alwin (Oxford University Press, 2018)
This article reviews the literature on contract farming (CF) in India and assesses the impact of smallholders’ perceived production risks on the adoption of CF; the impact of CF on smallholders’ food security; and its impact on employment generation in their farming enterprises. We also show the impact of the outcome variables by risk preference of smallholders. Using farm‐level data and endogenous switching regression methods, this study presents three key findings. First, the perception of weather and pest risk, access to irrigation facilities, extension visits, and access to institutional credit are the main drivers of CF adoption. Second, CF adoption increases food security and varies with the revealed risk preference of smallholders, and risk‐seeking smallholders tend to gain higher food security. Third, regardless of revealed risk preferences, smallholders who did not adopt CF benefit from adoption by reducing their labor requirements, with no significant losses in yield.